PANDANGAN KEPALA SEKOLAH MENGENAI PENDIDIKAN INKLUSIF DAN ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR DIY - Dinar Westri Andini; Ayu Rahayu; C Asri Budiningsih; Mumpuniarti Mumpuniarti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
The right view of inclusive education is very influential on the success of the implementation of inclusive education, starting from the policies applied, routines that will bring up a culture of acceptance of diversity and the implementation of classroom learning. The principal becomes the agent of change and as the main key in the development, initiator of innovation and decision making on the implementation of inclusive education until the realization of the success of the implementation practices in school. The purpose of this study is to explain the principal's view of inclusive education in Yogyakarta Elementary School. Questionnaires were distributed to 25 principals in elementary schools in five districts in Yogyakarta Special Region. The results showed that the majority of principals in SD DIY have a narrow view of inclusive education, which is still limited to the acceptance of children with special needs, but the majority of principals agree and are open that children with special needs for school and study together with other children in the classroom regular / general.